Mechanism Of Land Right Transfer In Sale And Purchase Agreements (Study At The Notary And PPAT Office Dewi Faraditha, S.H., M.Kn, Bogor Regency) - Haryanto, Tasya Annisa; Purwaningsih, Prihatini (JURNAL MAHASISWA YUSTISI, 2025)
The transfer of land rights through sale and purchase is one of the most common forms of rights transfer in land practice in Indonesia. However, in practice, various administrative and legal issues often arise, particularly related to procedures and document validity. This research aims to analyze the mechanism of land rights transfer in sale and purchase agreements conducted by the Notary Office and Land Deed Official (PPAT) Dewi Faraditha, S.H., M.Kn in Bogor Regency, as well as to identify the obstacles encountered and the solutions applied. The research method used is empirical juridical with a qualitative approach, where data is obtained through literature study and direct interviews with relevant parties. The research results show that the mechanism for the transfer of land rights at the PPAT office has followed the procedures as regulated in Government Regulation Number 24 of 1997 concerning Land Registration, which includes certificate verification, the creation of sale and purchase deeds, tax payment, and the name transfer process at the land office. The obstacles faced include discrepancies between physical and juridical data, administrative delays, and a lack of legal understanding from the parties involved. The resolution carried out by the PPAT and the agency involves conducting a thorough document verification and providing legal assistance to the parties involved. Thus, the role of notaries and PPAT is crucial in ensuring legal certainty in land sale and purchase transactions.